Comparison of muscle energy technique and facet joint mobilisation in the patient with chronic neck pain: A randomized controlled trial - Huma Tabassum; Mariam, Misbah; Gondal, Kirran Sikandar (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the effects of muscle energy techniques, facet joint mobilisation and conventional physical therapy on pain, disability, cervical lordosis and range of motion in patients with chronic neck pain. Method: The parallel-design randomised controlled trial was conducted at the Physical Therapy and Rehabilitation Department of the Heavy Industries Taxila Hospital, Taxila Cantt, Pakistan, from December 2020 to May 2021, and comprised patients of either gender aged 35-50 years who had chronic neck pain, recurrent neck pain, and cervical spine curve. The participants were randomised into muscle energy techniques group A, facet joint mobilisation group B and conventional physical therapy group C. The outcome measures were cervical lordosis, pain intensity, neck disability index and cervical range of motions. Data was analysed using SPSS 21. Results: Of the 115 patients initially assessed, 105(91.3%) were included; 67(63.8%) females and 38(36.2%) males. There were 35(33.3%) subjects in group A with mean age 40.09± 4.29 years, 35(33.3%) in group B with mean age 40.14±4.57 years and 35(33.3%) in group C with men age 39.26±5.19 years. There were no significant differences among the groups at baseline in terms of mean age, weight, height, body mass index, neck disability index, cervical lordosis and range of motion (p>0.05). Of the total, 6(5.7%) were lost to follow-up and the study was completed by 99(94.3%) subjects. Outcome variables in group A were superior to those in groups B and C with respect to flexion, rotation and side-bending (p<0.05). There was no significant difference between groups A and B related to numeric pain rating scale and neck disability index (p>0.05). Conclusion: Muscle energy techniques and facet joint mobilisation showed significant improvement in neck pain, disability and cervical range of motions compared to conventional physical therapy. Muscle energy techniques and facet joint mobilisation produced similar outcomes with respect to pain intensity and functional disability. Clinical Trial Number: The study was prospectively registered with clinicaltrials.gov (NCT05040477). Key Words: Cervical lordosis, Facet joint, Mobilisation, Muscle energy techniques, Neck pain.